Protein characterization by biochemical analysis: MKP3 binding and auto-inhibitory functions Unexpected lability in the SARS nucleocapsid protein - Mark, John K (University of Ottawa (Canada), 2008)
Two proteins were tested using biochemical assay techniques to determine the reasons for their loss of function or loss of primary structure. The first protein that was analysed, MAP kinase phosphatase 3 (MKP3), dephosphorylates the extracellular signal-regulated kinases (ERKs). Dephosphorylation occurs following ERK binding to MKP3's N-terminal domain, which activates MKP3's allosteric C-terminal phosphatase domain. To determine the mechanism for MKP3's loss of function in pancreatic adenocarcinoma cells, experiments were conducted to test the effect of potential protein-protein interactions on MKP3 activity. Surface plasmon resonance binding studies using the full-length MKP3 and N- and C-terminal truncation mutants showed that the N- and C-terminal MKP3 domains could bind with a dissociation constant (KD) of 1.43 +/- 0.41 muM. The low KD value between the two domains is consistent with the presence of an interdomain binding site. A novel MKP3 activity assay was then developed to test if the binding affected MKP3's phosphatase activity. Chemically-activated MKP3 C-terminal domain was capable of hydrolysing p-nitrophenol phosphate with a catalytic efficiency (kcat/KM) ∼33% greater than the full-length MKP3 protein. However, when MKP3 C-terminal domain activity was tested in the presence of the N-terminal domain, the addition led to a dose-dependant inhibition with a KI (inhibition constant) of 0.68 +/- 0.37 muM. The similarity between the KD and K I constants, for MKP3's N- and C-terminal binding and inhibition, implies that MKP3 interdomain binding results in inhibition of MKP3 activity. This finding was compared to experiments showing that pancreatic adenocarcinoma cells contain a non-functional, wild-type MKP3 that forms high molecular weight oligomers. Biochemical analysis and the detection of the oligomers indicates that MKP3 overexpression in adenocarcinomas may lead to a loss of enzyme function through intercalation of N- and C-terminal domains via a "domain swap" interaction that results in MKP3 autoinhibition. The second study was performed on the SARS nucleocapsid (N) protein. N protein displayed an unexpected lability and multiple lower molecular weight bands were detected upon N protein purification. Mass spectrometry was used to identify the bands as the N- and C-terminal fragments of SARS N protein, which result from a specific cleavage after each arginine in the N protein's 184SSRSSSRSRGNSR196 sequence. Fluorescent resonance energy transfer (FRET) based assays that were developed to test for non-specific protease activity showed negative results. This may indicate that the SARS N protein possesses a specific autocatalytic activity.
Keywords: Chemistry, Biochemistry.